The Aesthetic Path to Hermeneutics in J.-L. Marion’s Phenomenology - Roggero, Jorge Luis (2023)
Jean-Luc Marion has recently developed the role of hermeneutics in his phenomenology of givenness.This paper aims to demonstrate that there is an aesthetic path to access the hermeneutical basic operation in Marion’s previous work. The Marionian hermeneutical management of the gap between what gives itself and what shows itself finds its heuristic model in the artist’s task of turning visible the unseen, as can be found in his studies on painting.